2014
DOI: 10.1364/boe.5.001355
|View full text |Cite
|
Sign up to set email alerts
|

Photo-induced processes in collagen-hypericin system revealed by fluorescence spectroscopy and multiphoton microscopy

Abstract: Collagen is the main structural protein and the key determinant of mechanical and functional properties of tissues and organs. Proper balance between synthesis and degradation of collagen molecules is critical for maintaining normal physiological functions. In addition, collagen influences tumor development and drug delivery, which makes it a potential cancer therapy target. Using second harmonic generation, two-photon excited fluorescence microscopy, and spectrofluorimetry, we show that the natural pigment hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…HYP has recently received increasing attention due to its high phototoxicity against viruses and malignant cells. [28][29][30] In addition, it has been shown that HYP is an effective sensitizer for selective light-controlled collagen modification in connective tissues, 31,32 which is important for therapy of collagen-related disorders and tissue engineering. However, HYP molecules aggregate in water or blood, form nonsoluble, nonfluorescent complexes, and lose photosensitizing, antitumor properties.…”
Section: Discussionmentioning
confidence: 99%
“…HYP has recently received increasing attention due to its high phototoxicity against viruses and malignant cells. [28][29][30] In addition, it has been shown that HYP is an effective sensitizer for selective light-controlled collagen modification in connective tissues, 31,32 which is important for therapy of collagen-related disorders and tissue engineering. However, HYP molecules aggregate in water or blood, form nonsoluble, nonfluorescent complexes, and lose photosensitizing, antitumor properties.…”
Section: Discussionmentioning
confidence: 99%
“…Take the case of tumors, for example, some PSes compromise tumor cells mainly in an indirect way, damaging the tumor vasculature and blocking the supply of molecular oxygen and essential nutrients. This effect is associated to binding of the hydrophilic/water soluble PSes to serum albumin, since it mediates PS accumulation in vascular stroma, or to binding to vascular structures/constituents, such as collagen [ 170 , 171 , 172 ]. On the other hand, there is evidence that highly hydrophobic PSes act in tumors mostly by direct interactions, since they are usually transported inside the body by association to low density lipoproteins (LDL), which can deliver them to intracellular sites [ 172 , 173 , 174 ].…”
Section: Parameters Determining Photosensitizer (Ps) Efficiencymentioning
confidence: 99%
“…Hyp has recently received increasing attention due to its high phototoxicity against viruses and anti-tumour photoreactivity 30 41 42 43 . In addition, it is shown that Hyp is an effective mediator for light-controlled selective modification of collagen in connective tissues, and may be used in biomedical engineering and therapy of collagen-related disorders 44 45 . However, Hyp in PBS and pure water tends to aggregate and form non-soluble and non-fluorescent complex thereby losing its tumour-selective properties 46 .…”
Section: Discussionmentioning
confidence: 99%